Enhancing EFL learners’ speaking skills through the mingle activity: a qualitative study of perceptions and classroom implementation - Wahyuni, Lilis Sri Wahyuni; Siti Maysuroh; M. Adib Nazri; Ayu Surayya (Mell Baou Publisher, 2025)
Speaking is a crucial skill in English learning, yet many EFL learners struggle due to limited confidence, vocabulary, and opportunities for practice. This study examined the implementation of the Mingle Activity and explored students’ perceptions of its contribution to improving their speaking skills. Using a qualitative descriptive design, the research involved 15 participants (10 students and 5 tutors) from an English course in NTB. Data were gathered through questionnaires, interviews, observations, and documentation, and analyzed using SPSS alongside data reduction, data display, and conclusion drawing techniques. The findings indicate that students held positive perceptions of the Mingle Activity, reporting increased confidence, fluency, and motivation to speak English. Interactive tasks such as group discussions and presentations were particularly engaging. Although learners faced challenges such as limited vocabulary and speaking anxiety, their overall enthusiasm remained high. Observations revealed active participation, while tutors facilitated learning by guiding discussions and encouraging less confident students. Supporting documentation—including photos, videos, and vocabulary lists—demonstrated noticeable progress in speaking performance. The Mingle Activity effectively enhanced students’ speaking skills by fostering interactive and supportive communicative practices. These results are consistent with Vygotsky’s sociocultural theory and Communicative Language Teaching, both of which highlight the importance of peer interaction and authentic language use.